COMPUTERIZED SYSTEM ADMINISTRATION EDUCATION IN INDONESIA MANAGEMENT DEVELOPMENT INSTITUTE - Siti Wardah; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 1996)
Computerization as an alternative to meet the smoothness and timeliness in confectionery a system of educational administration Indonesian Institute for Management Development. Use of existing computers as data processing devices, the improvement of educational administrative services IPMI capabilities can be realized.